PROBLEMS HINDERING STUDENT TEACHERS’ ELT MATERIALS DEVELOPMENT: A STUDY IN THE INTERNSHIP PROGRAM IN EASTERN INDONESIA - Yakob Metboki (English Review: Journal of English Education, 2018)
In the sense of running qualified teaching and learning, teacher education institutions place their student teachers at schools to experience real teaching practices through the internship program. This study aims to give a comprehensive portrait of problems the student teachers of English have when they develop ELT materials and how the problems vary according to different areas. The present study applied qualitative method. It utilized survey as data collection technique. Twenty-five student teachers are recruited as participants. Having conducted the survey, the results showed that most student teachers have several problems in developing ELT materials during internship program. The biggest problem lies on developing material for practicing grammar elements (2.98 level of difficulty). The participants simply felt it easy to develop material for grading and recycling, and supporting materials with ranging from 3.22 and 3.10 level of difficulty. The following problem lies on how the material promotes the development of language skills and communicative abilities. Overall, the present study indicates that the student teachers are still lacking of grounded concepts on what and how to develop ELT materials that fit to students’ needs. Keywords: English language teaching; materials development; internship program; students-teachers’ problems; survey.